Distribution, source apportionment and ecological risks of organophosphate esters in surface sediments from the Liao River, Northeast China. (July 2020) - Luo, Qing; Gu, Leiyan; Wu, Zhongping; Shan, Yue; Wang, Hui; Sun, Li-na
Abstract: A total of 24 surface sediment samples were collected from Liao River, Northeast China. The concentration, spatial distribution, potential source, and ecological risk of 13 organophosphate esters (OPEs) flame retardants and plasticizers were analyzed. The total concentrations of OPEs varied considerably, ranging from 19.7 to 234 ng g −1 dry weight (dw), with the mean concentrations of 64.2 ± 52.2 ng g −1 dw. The OPEs pollution was increasing from upstream to downstream of Liao River. Compared with other sediments of rivers and lakes all over the world, Liao River has been seriously contaminated by OPEs, especially tributyl phosphate (TNBP) and tri-butoxyethyl phosphate (TBOEP). TNBP was the most abundant OPEs, followed by TBOEP and triphenylphosphine oxide. Their mean relative contributions were 26.3%, 12.4% and 11.6%, respectively. Positive matrix factorization indicated that OPEs in sediments from Liao River might be derived from plastic, textile, and polyurethane foam, anti-foam agent, hydraulic fluids, and coatings, indoor release, and chemical process emission. The risk of potential adverse effects of each individually OPEs on aquatic organisms were low (risk quotient less than 0.1). 2-Ethylhexyl diphenyl phosphate was the main substance causing risk. Graphical abstract: Image 1 Highlights: The 13 targets OPEs were detected in surface sediment samples from Liao River with 100% detection frequency. The OPEs pollution was increasing from upstream to downstream of Liao River. Liao River has been seriously contaminated by OPEs, especially TNBP and TBOEP. TNBP was the most abundant OPEs, followed by TBOEP and TPPO. EHDPP was the main substance causing risk.